Impact of Google Classroom and Google Forms as Learning Media on Students' Interest and Learning Outcomes - Fera Widia Sari, Muhajir, Soubar Isman (Journal of Educational Studies, 2025)
The purpose of this research is to examine how the use of learning media affects the motivation and performance of SMAN 4 Pamekasan grade X English students. A total of 36 students from two courses made up the study sample. Google Classroom was the medium via which the study's instructors sent course materials and other information to their students. Questionnaires, exams, and records were used to gather data in a quantifiable manner. Using random selection procedures, the classes that would later become the control and experimental groups were chosen. The findings demonstrated that students' interest and learning outcomes were impacted by the utilisation of Google Classroom as a learning medium, in comparison to the non-using group. The results show that in class XI at SMAN 4 Pamekasan, there was a notable disparity in learning interest scores (0.045 < 0.05) and learning outcome scores (0.014 < 0.05) when Google Classroom and Google Forms were used.A more successful digital learning method may be implemented by schools, instructors, and students via the usage of Google Classroom and Google Forms, which have been shown to enhance student engagement and learning results.